Very rapid flow cytometric assessment of antimicrobial susceptibility during the apparent lag phase of microbial (re)growth. Issue 4 (11th February 2019) - Jindal, Srijan; Thampy, Harish; Day, Philip J. R.; Kell, Douglas B.
Abstract : Rapid changes in the number and flow cytometric behaviour of cells of E. coli taken from a stationary phase and inoculated into rich medium. Abstract : Cells of E. coli were grown in LB medium, taken from a stationary phase of 2–4 h, and re-inoculated into fresh media at a concentration (10 5 ml −1 or lower) characteristic of bacteriuria. Flow cytometry was used to assess how quickly we could detect changes in cell size, number, membrane energization (using a carbocyanine dye) and DNA distribution. It transpired that while the lag phase observable macroscopically via bulk OD measurements could be as long as 4 h, the true lag phase could be less than 15–20 min, and was accompanied by many observable biochemical changes. Antibiotics to which the cells were sensitive affected these changes within 20 min of re-inoculation, providing the possibility of a very rapid antibiotic susceptibility test on a timescale compatible with a visit to a GP clinic. The strategy was applied successfully to genuine potential urinary tract infection (UTI) samples taken from a doctor's surgery. The methods developed could prove of considerable value in ensuring the correct prescription and thereby lowering the spread of antimicrobial resistance.